Pendampingan Penyusunan Laporan Keuangan Masyarakat atau Produsen Budidaya Jamur Tiram Dalam Meningkatkan Penghasilan Keluarga di Desa Kurungan Nyawa I - Rifa'i, Muhamad Nanang; Ismail, Khafid; Anam, Syaiful (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2021)
This dedication is motivated because the preparation of financial report books for oyster mushroom cultivation in Kurungan Nyawa I village has not been maximized, even though 60% of the villagers have been in this business for quite a long time for the last 5 years. So far, bookkeeping is only written on a piece of paper and is likely to be lost. Some concrete solutions offered in the outreach program to the community regarding assistance in preparing financial reports for oyster mushroom cultivation are (socialization, training, and monitoring). The results of this activity include: 1) being able to produce bookkeeping correctly 2) being able to help bookkeeping management so that it looks neat. With the orderly management of financial statements, it will affect the stability of the oyster mushroom cultivation so that it can improve the family economy.